Diet breadth of fish communities in Vamanapuram river, Kerala, South India - S. David Kingston (Hawassa University, 2021)
An understanding of the feeding habits of fish species in natural environment gives clues for selecting the species for aquaculture. It helps in formulating artificial feeds for culturing species under artificial conditions for small scale or large scale aquaculture. The main objective of the present study was to find the food preferences of fish species in different ecological niches such as low land streams, riverine and estuary. Stomachs were cut, food items removed and stored in 4% formalin. Diet breadth was calculated as per the standard methods widely recommended. The diet breadth calculated for the fish assemblages in Vamanapuram River showed that Puntius amphibius has the highest breadth of 6.64. The surface feeding fishes had low diet breadth which ranged from 1.13-1.83. Their main food has been observed to be terrestrial insects. The generalists like Rasbora daniconius and Puntius filamentosus have diet breadth of 3.27 and 4.15, respectively. Whereas fish species found in estuarine habitats showed diet breadth range from 1.00 to 2.82. The fishes present in the upper regions of the river habitat were observed to have low diet breadth than lowland streams. In general, high diet breadth values were observed during February to May. The breadth of Barilius bakeri showed minor variations among the three seasons (1.00 to 1.20). Based on the diet breadth, the majority of the fishes in Vamanapuram River generalists